Biografia edukacyjna malgaskich uczniów – badania wstępne - Lendzion, Kinga (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
In this article, the author attempts to look at the stage of schooling through the eyes of young Malagasy people. To this end, she presents the results of a preliminary biographical study, embedded in the current of indigeneous methodology, conducted among Malagasy senior students in two selected high schools in Madagascar. The students were asked to write essays on the history of their education. The biographical essays of the students tell a common narrative centred around three stages of education: primary school, middle school, and secondary school. The young people tell about difficult situations in their education and family life, paying particular attention to adolescence.